Regularity criteria for the Navier–Stokes equations based on one or two items of the velocity gradient. (December 2017) - Skalák, Zdeněk
Abstract: We study the regularity criteria for the incompressible Navier–Stokes equations based on either one item of the velocity gradient, ∂ 1 u 3 or ∂ 3 u 3 or on two items of the velocity gradient, ∂ 2 u 3, ∂ 3 u 3, or ∂ 1 u 3, ∂ 2 u 3 . We improve and/or extend several results from the literature by the use of two versions of the generalized Troisi inequality.